Long-term oral antiarrhythmic therapy with mexiletine. - Campbell, N P (1978)
Forty-eight patients with ischaemic heart disease received oral mexiletine for the control or prevention of ventricular arrhythmias. The most frequently used doses were 200, 250, and 300 mg 8-hourly. The treatment period varied from 2 days to more than 1 year (median 3 months). No ventricular arrhythmias were detected in more than one-half of the patients. Severe side effects occurred in 15 (31%) of the 48 patients. Major ventricular arrhythmias were observed in 14 (29%) of the 48 patients at a time when the majority had plasma concentrations within the therapeutic range. The value of mexiletine in the management of patients at risk of sudden death is likely to be limited.